2023
DOI: 10.3390/biomedicines11061721
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Inhibits Proliferation and Induces Autophagy of Tumor Cells in Pleural Effusion of Patients with Non-Small Cell Lung Cancer Expressing EGFR with or without Mutations via PI3K/AKT/mTOR Pathway

Abstract: To clarify whether arsenic could exert inhibitory effects on tumor cells in pleural effusions of patients with non-small cell lung cancer (NSCLC), 36 NSCLC pleural effusion samples were collected from Changzheng Hospital and Ruijin Hospital, from 2019 to 2022. The genotype of epidermal growth factor receptor (EGFR) was identified. Tumor cells were isolated and treated with arsenic trioxide (ATO) or/and gefitinib. Additionally, six patients were intrapleurally administrated with ATO. Results showed that 25 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…For example, several studies showed that Akt inhibition induced apoptosis in A549 lung adenocarcinoma cells [49][50][51][52]. In addition, inhibition of mTOR signaling was demonstrated to induce autophagy in lung adenocarcinoma [53][54][55]. Moreover, studies emphasize the role of PI3K signaling and PTEN in the promotion of migration, invasion and metastasis in lung adenocarcinoma [56][57][58].…”
Section: Mtor Signaling In Nsclc Pathobiologymentioning
confidence: 99%
“…For example, several studies showed that Akt inhibition induced apoptosis in A549 lung adenocarcinoma cells [49][50][51][52]. In addition, inhibition of mTOR signaling was demonstrated to induce autophagy in lung adenocarcinoma [53][54][55]. Moreover, studies emphasize the role of PI3K signaling and PTEN in the promotion of migration, invasion and metastasis in lung adenocarcinoma [56][57][58].…”
Section: Mtor Signaling In Nsclc Pathobiologymentioning
confidence: 99%